Highly Efficient Layered Double Hydroxide-Derived Bimetallic Cu-Co Alloy Catalysts for the Reverse Water-Gas Shift Reaction - Kim, Kwang Young; Jang, Wonsik; Byun, Woo Jin; Lee, Ji Young; Kim, Miri; Lee, Ju Hyeong; Rhim, Geun Bae; Youn, Min Hye; Chun, Dong Hyun; Kim, Seok Ki; Cho, Seungho; Lee, Jae Sung (ACS Catalysis, 2024)
Bimetallic alloy catalysts with finely controlled composition and atomic mixing of the two active metals are vital for maximizing their synergistic effect in enhancing catalytic performances. Herein, we report the design and synthetic strategy of bimetallic Cu-Co alloy catalysts well dispersed on Al2O3 from a CuCoAl-layered double hydroxide (LDH) for boosting the reverse water-gas shift (RWGS) performance by controlling the composition and textural properties of Cu-Co alloy particles. An optimized Cu9Co1/Al2O3 catalyst exhibits a remarkably high CO2 to CO conversion rate (∼0.247 mol h-1 gcat-1) with ∼99.4% of CO selectivity at a relatively low reaction temperature of 400 °C, which outperforms a monometallic Cu/Al2O3 catalyst and a reference Cu9Co1/Al2O3 catalyst prepared by a conventional impregnation method. A combined experimental and theoretical study reveals that the superior activity of the Cu9Co1/Al2O3 catalyst is attributed to two factors: (i) a modified electronic structure due to the Cu-Co alloy formation that facilitates CO2 activation and CO desorption and (ii) formation of well-dispersed alloy nanoparticles by using LDHs as the catalyst precursors.
Keywords: Alloy catalyst; Atomic mixing; Bimetallic alloys; Bimetallics; Catalytic CO2 hydrogenation; Cu-co alloy catalyst; Layered-double hydroxides; Reverse water-gas shift reaction; Well-dispersed; ]+ catalyst; catalytic CO2 hydrogenation; Cu-Co alloy catalysts; layered double hydroxide; reverse water-gas shift reaction